A Novel BODIPY Quaternary Ammonium Salt-Based Fluorescent Probe: Synthesis, Physical Properties, and Live-Cell Imaging - Deng, Peng; Xiao, Fuyan; Wang, Zhou; Jin, Guofan (Frontiers in Chemistry, 2021)
The development of biological fluorescent probes is of great significance to realize the cancer bio-imaging. However, most of current probes with bulky hydrophobic group limited the application in aqueous medium and restricted the imaging under physiological conditions. Herein, we proposed two efficient molecular to study their physical properties and imaging work, and the absorption and fluorescence intensity were collected with varying ion attending in aqueous medium. We enhance the water solubility through the quaternization reaction and form the balance between hydrophilic and hydrophobicity with dipyrrome-theneboron difluoride (BODIPY) fluorophore. We introduced pyridine and dimethylaminopyridine (DMAP) by quaternization and connected the BODIPY fluorophore by ethylenediamine. The final synthesized probes have achieved ideal affinity with HeLa cells (human cervical carcinoma cell line) in live-cell imaging which could be observed by Confocal Microscope. The probes also have a good affinity with subcutaneous tumor cells in mice in in vivo imaging, which may contribute to be the candidates of oncology imaging probes.